EXPLORATORY FACTOR ANALYSIS OF SELF-CARE AMONG MALAYSIAN HEART FAILURE PATIENTS - Ismail, Wan Marina Wan (International Journal of Psychosocial Rehabilitation, 2020)
Self-care has come to mean different things to other people due to individual beliefs and perspectives. On the multidimensional aspects of the self-care construct, heart failure self-care behaviours are the coping process that individuals with heart failure performs to maintain their health and control to their symptoms in response to their diseases. The performance of self-care behaviours in the heart failure population have improved outcomes in physical and emotional aspects towards quality of life.The purpose of this study is to assess the Self- Care of Heart Failure Index (SCHFI) among Malaysian. The study used a non-experimental quantitative design with a theoretical framework based on the Self Care of Heart Failure model. Random sampling was carried out, whereby the population in this pilot study came from the medical clinic and Ccardiology department of two tertiary and secondary hospitals. Data were collected for four weeks in these hospitals. The total number of respondents in this pilot study was 200. SPSS version 21.0 was used to analyse the data. The instrument was divided into three components; namely self-care confidence, self-care management, and self-care maintenance. Overall, the scale consisted of 22 items. The SCHFI was translated into Bahasa Malaysia using translation procedures conducted by experts in their fields. The results of the exploratory factor analysis (EFA) found all 21 items acceptable due to factor loading of greater than 0.6.However, only question number 16 from the self-care management component had a loading factor of 0.69. In conclusion, for local content, the items measuring the construct in respective components were rearranged accordingly before proceeding with data collection in the field study.